PERAN JOB SATISFACTION DALAM MEMEDIASI PENGARUH BUDAYA ORGANISASI TERHADAP KOMITMEN ORGANISASI (Studi Kasus Pada Karyawan Billman PT.Penkalis Sridanta ULP.Gianyar) - Ni Rai Riska Yudiani; Ni Made Yudhaningsih; Ngurah Arya Suryadhana (STIMI Handayani Denpasar, 2022)
The purpose of this study is to know how organizational power affects organizational commitment and job satisfaction, to know how job satisfaction affects an organization's commitment, and how the role of occupational satisfaction affects an organization's commitment. The study was conducted at sridanta's pedicular factory in billman's employee ulp gianyar with a sample of 51 employees' studies. His data-collection techniques are observation, interview, documentation, literature methods and questionnaires. Whereas the data analysis techniques are the validity, reliability, path analysis and sobel test test. Research shows the organization's culture has had a positive and significant impact on the organization's commitment, The value b1 of 0.547 was obtained and the significance of 0,000 less than 0.05. The organizational culture affects positive and significant job satisfaction as it achieves a value b2 of 0.193 and a degree of significance of 0.003 smaller than 0.05. Job satisfaction has a positive and significant impact on the organization's commitment as it gains a value of 1.123 and a degree of significance of 0,000 less than 0.05. Job satisfaction capable of undermining the organization's cultural impact on the organization's commitment to z-counting (3.13) > z-table (1.675), in other words work satisfaction is the intering variable that links the organization's culture with the organization's commitment.